The Factors Dictating Properties of Atomically Precise Metal Nanocluster Electrocatalysts. Issue 23 (10th April 2022) - Yan, Hao; Xiang, Huixin; Liu, Jiaohu; Cheng, Ranran; Ye, Yongqi; Han, Yunhu; Yao, Chuanhao
Abstract: Metal nanoparticles occupy an important position in electrocatalysis. Unfortunately, by using conventional synthetic methodology, it is a great challenge to realize the monodisperse composition/structure of metal nanoparticles at the atomic level, and to establish correlations between the catalytic properties and the structure of individual catalyst particles. For the study of well‐defined nanocatalysts, great advances have been made for the successful synthesis of nanoparticles with atomic precision, notably ligand‐passivated metal nanoclusters. Such well‐defined metal nanoclusters have become a type of model catalyst and have shown great potential in catalysis research. In this review, the authors summarize the advances in the utilization of atomically precise metal nanoclusters for electrocatalysis. In particular, the factors (e.g., size, metal doping/alloying, ligand engineering, support materials as well as charge state of clusters) affecting selectivity and activity of catalysts are highlighted. The authors aim to provide insightful guidelines for the rational design of electrocatalysts with high performance and perspectives on potential challenges and opportunities in this emerging field. Abstract : Due to the merits of well‐defined composition and structure, metal nanoclusters provide an excellent platform to study the correlations between their structures and properties at the atomic level. In this review, the factors (e.g., size, metal doping/alloying, ligand engineering, support materials, and the charge state of clusters) that affect the electrocatalytic properties of catalysts are highlighted and perspectives on potential challenges and opportunities are discussed.